VARIOUS SPECTRUM OF OCULAR TUBERCULOSIS - Haq, Aqdus; Shaheen, Fiza; Farooq, Saadia (Journal of Ayub Medical College Abbottabad, 2021)
Mycobacterium Tuberculosis may infect any organ in the body, when it affects ocular tissue symptoms are vague and hence diagnosis is challenging, through a number of cases reported in our clinic it is emphasized to make quantiferon test as part of routine investigation for cases of presenting with uveitis thus leading to timely diagnosis and accurate treatment.